Pressure changes in the endotracheal tube cuff in otorhinolaryngologic surgery: a prospective observational study - Park, Sujung; Kwon, Young In; Kim, Hyun Joo (Frontiers in Medicine, 2023)
Objective Inflation of the endotracheal tube cuff is needed for providing ventilation. Cuff pressure should be maintained inside the appropriate range to prevent critical airway complications. The purpose of this study is to evaluate the pressure changes in the endotracheal tube cuff during otorhinolaryngologic surgery. Design and method This single-center observational study was conducted at Severance Hospital in Korea between April 2020 and November 2020. Patients aged >20 years scheduled to undergo otorhinolaryngological surgical procedures were enrolled. Patients undergoing planned tracheostomy and those who were slated for uncuffed endotracheal tube use were excluded. Intubation was performed after the induction of general anesthesia. A pressure transducer was connected to the pilot balloon of the endotracheal tube, and cuff pressure was continuously monitored until extubation. If the cuff pressure was not appropriate for more than 5 min, it was adjusted to the appropriate range by injecting or removing air. The percentage of time for which the cuff pressure remained within the appropriate range was calculated and defined as the time in the therapeutic range (TTR). The presumed cause for the rise or fall in cuff pressure was identified. Results In total 199 patients, alterations in cuff pressure outside the appropriate range occurred in 191 patients (96.0%). The mean TTR was 79.7% (SD 25.0%), and head and neck surgery had the lowest mean TTR of 69.0% compared to ear and nose surgeries (94.2 and 82.1%, respectively). Sixty-eight patients (34.2%) demonstrated inadequate endotracheal tube cuff pressure for more than 20% of the total anesthesia time. Twenty-six patients (13.1%) demonstrated optimal endotracheal tube cuff pressure for less than 50% of the total anesthesia time. The causative factors inducing inappropriate cuff pressure were found to vary, including positional changes, surgical procedure, anatomical manipulation, and anesthetic procedure. Conclusion In otorhinolaryngologic surgery, cuff pressure increased or decreased outside the appropriate range due to various factors. Therefore, we suggest close continuous monitoring of cuff pressure during anesthesia for otorhinolaryngologic surgery. Clinical trial registration clinicaltrials.gov, identifier NCT03938493.